Business and academic cooperation: an innovative proposal in the promotion of historical archaeology. - Ortiz Ortiz, Mauricio (2021)
In the district of Cureña of Sarapiquí, C.R., at the site known as La Trinidad, a project was carried out for the purpose of recuperating and interpreting cultural evidence of the battle that took place there in 1856-1857. Archaeological research had to be undertaken in order to complement the historical documents that attest the combat. This article comments on the genesis of the project, the people involved, as well as organizations and institutions that provided their support in the different stages of the study, as an example of an alliance between private companies and the cultural sector. This effort was required for a project of this nature to be successful. Since it is a pioneer archaeological study of a battle in C.R., the details of preceding and generating elements of the historical knowledge obtained are important, as well as applications of such knowledge to the development of Sarapiquí and Costa Rica.